Gambaran Pengetahuan Pengasuh Tentang Pijat Common Cold di Panti Asuhan Manarul Mabrur: Overview of Caregivers' Knowledge About Common Cold Massage at Manarul Mabrur Orphanage - Bela Catur Sakti Rahayu; Rini Susanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2024)
The most common health problems experienced by toddlers are coughs and colds caused by irritation of the respiratory tract, allergies, weakened immune systems and poor environments. Coughs and colds in children if not treated immediately can result in serious complications. Caregivers at the Manarul Mabrur Orphanage experience fluctuations, where caregivers drop out because they work voluntarily. Every day 5 out of 24 toddlers who live in one room experience coughs and colds. The treatment carried out by the orphanage when toddlers are sick with coughs and colds is only given telon oil or body warmers until they recover on their own because they are considered to be just common flu. Lack of knowledge of caregivers in treating coughs and colds with non-pharmacological baby massage that can be done by yourself and also saves on treatment costs causes the treatment of coughs and colds to be delayed. This study aims to determine the knowledge of caregivers regarding common cold baby massage at the Manarul Mabrur Orphanage. With the existence of non-pharmacological cough and cold treatment that can be done by yourself and also saves on treatment costs for the orphanage. The method used in this study is descriptive with a location at the Manarul Mabrur Orphanage on July 21-28, 2023. The sample in this study was the entire population taken, namely, all caregivers of the Manarul Mabrur Orphanage as many as 7 respondents who were in the orphanage when the study was conducted. The results of the study showed that most of the caregivers' educational level regarding common cold massage at the Manarul Mabrur Orphanage, most of the knowledge was lacking at the basic education level of 5 caregivers (71.4%) ABSTRAK Gangguan kesehatan yang paling sering dialami bayi balita adalah batuk pilek yang disebabkan oleh iritasi saluran pernapasan, alergi, melemahnya daya tahan tubuh dan lingkungan yang buruk. Batuk pilek pada anak apabila tidak segera ditangani dengan baik dapat berakibat pada terjadinya komplikasi yang memberatkan. Pengasuh di Panti Asuhan Manarul Mabrur mengalami fluktuatif, dimana pengasuh drop out karena bekerja dengan sukarela. Setiap harinya 5 dari 24 balita yang tinggal dalam satu ruangan mengalami batuk pilek. Penanganan yang dilakukan pihak panti ketika balita sakit batuk pilek hanya diberikan minyak telon atau penghangat badan sampai sembuh dengan sendirinya karna dianggap hanya flu biasa, serta kurangnya pengetahuan pengasuh dalam pengobatan batuk pilek dengan non farmakologi pijat bayi yang dapat dilakukan sendiri dan juga menghemat biaya perawatan ini menyebabkan penganganan batuk pilek terlambat. Penelitian ini bertujuan untuk mengetahui pengetahuan pengasuh mengenai pijat bayi common cold di Panti Asuhan Manarul Mabrur. Dengan adanya pengobatan batuk pilek non farmakologi yang dapat dilakukan sendiri dan juga menghemat biaya perawatan pihak panti. Metode yang digunakan dalam penelitian ini adalah deskriptif dengan lokasi di Panti Asuhan Manarul Mabrur pada tanggal 21 – 28 Juli 2023. Sampel dalam penelitian ini adalah seluruh dari populasi yang diambil yaitu, seluruh pengasuh Panti Asuhan Manarur Mabrur sebanyak 7 responden yang berada di panti saat dilakukan penelitian. Hasil penelitian didapatkan bahwa sebagian pengasuh tingkat pendidikan pengasuh tentang pijat common cold di Panti Asuhan Manarul Mabrur sebagian besar pengetahuan kurang pada tingkat pendidikan dasar sebanyak 5 pengasuh (71,4%)